A citation analysis of the Philippine Journal of Nutrition, 2001-2011 - Sabio, Mae Shaani S. (2013)
Journals are effective tools in publicizing updated information, and reflect interactions of information on a certain field of knowledge. This study used citation analysis to identify the current knowledge trends found in the Philippine Journal of Nutrition during the period of 2001-2011. Citation analysis is a practical basis for an effective collection development of libraries. Seventy-eight articles were analyzed and extracted a total of 1,530 citations. Data was encoded into a statistical software and then analyzed through frequency counts and descriptive statistics.